Policy options to achieve food security in South Asia - Mittal, Surabhi; Sethi, Deepti (Foundation Books, 2011)
Policy Options to Achieve Food Security in South Asia pulls together all South Asian countries and identifies major issues of food security in the individual country. The chapters highlight issues such as initiatives and policies taken up in these countries to achieve the goal of food security and also critically evaluate the effectiveness of these policies. It suggests measures to overcome the identified constraints and make the policies more effective. It also talks about the SAARC food bank to ensure food security in the region. The question of food security has a number of dimensions that go beyond production, availability and demand for food. Food availability does not ensure food security, thus distribution and access of population to food is equally important for food security. Food availability through better distribution mechanisms and alternatively through imports can ensure food security